Fault diagnosis of induction motors - Faiz, Jawad; Ghorbanian, Vahid; Joksimović, Gojko (IET energy engineering series, 2017)
This book is a comprehensive, structural approach to fault diagnosis strategy. The different fault types, signal processing techniques, and loss characterisation are addressed in the book. This is essential reading for work with induction motors for transportation and energy.